First report on the natural occurrence of entomopathogenic fungi in populations of the leafhopper Dalbulus maidis (Hemiptera: Cicadellidae): Pathogen identifications and their incidence in maize crops. Issue 12 (December 2021) - Souza, Daniela Aguiar; Oliveira, Charles Martins de; Tamai, Marco Antonio; Faria, Marcos; Lopes, Rogerio Biaggioni
Abstract: The corn leafhopper Dalbulus maidis is one of the most important pests of maize in Latin America. Here we report, for the first time, the natural occurrence of two fungal species infecting the adult stage of this pest. In 2020, insects killed by a pale bluish green fungus in irrigated maize fields located in Northeast Brazil were found attached to the abaxial surface of leaves. Using morphological characters and multigenic phylogeny, it was identified as Metarhizium brasiliense . In the beginning of 2021, the same pathogen was seen on adults in a maize field in the Central-Western region, alongside an entomophthoralean fungus during an epizootic. The latter pathogen was molecularly identified as a species in the genus Batkoa . The number of Batkoa -infected leafhoppers, displaying the typical swollen abdomen and extended wings, reached an average of 1.88 per maize leaf (86.42% of the sampled adults). The incidence of M. brasiliense was higher in plots in the Northeastern region (0.22 and 0.53 adult per leaf) when compared to the Central-Western region (0.04 adult per leaf). The report of D. maidis adults infected by M. brasiliense in agricultural settings located in different geographic regions and over 550 km apart indicates probable widespread occurrence of this pathogen in Brazil. Moreover, this opens the possibility of more applied biological control studies and, perhaps, the development of new tools to manage D. maidis populations. Highlights: - The natural occurrence of fungal entomopathogens on Dalbulus maidis is reported - Two fungal species were found infecting D. maidis adults in two regions of Brazil - Pathogens were identified as Batkoa sp. and Metarhizium brasiliense - Coepizootic of Batkoa sp. and M. brasiliense was detected in one of the corn fields